Morphofunctional Foot Characteristics of Chilean University Athletes in Ten Sports Disciplines [Características Morfofuncionales del Pie de Deportistas Universitarios Chilenos en Diez Disciplinas Deportivas] - Morales-Mauriz, H; Alarcon-Alvarez, E; Sanchez-Ramirez, C (Universidad de la Frontera, 2017)
It is known that there is great variability in the morphology of feet areas among different subjects. This is more evident in athletes, since the practice of sports subjects their feet to greater pressures and anatomical deformations, other than those exerted during daily life activities. It is clear therefore, that knowledge of the target population foot morphology is of high interest for the production of appropriate footwear to its shapes and dimensions. The objective of this research is to characterize morphological variables related to the feet of selected Chilean university athletes. The sample consisted of 169 subjects of both sexes of university population athletes of an average age of 23.27 years, 71 kilograms, 1.71 meters height and body mass index of 24.29. An anthropometer was used for measurements and the classification of the Medial Longitudinal Plantar Arch (MLPA) was performed by the Arch Index. It was shown that foot length corresponds to 15 % of the subject’s height. The Normal Forefoot Width (NFW) variable is equal to 39% of Foot Length (FL), with no differences between sexes. Posterior foot width corresponded to 25 % of LP; posterior foot Width is 63 % of the Forefoot Width (AA). Regarding the APLM, women presented values of normality located between 0.13 and 0.24 for left foot and 0.17 and 0.24 for right foot. The prevalence of flat foot was higher in men (25 % to 28%) than in women (4 % to 6 %) and the prevalence of cavus foot was higher in women (47 % to 53 %) than in men (27 % to 31 %). © 2017, Universidad de la Frontera. All rights reserved.